Challenges to Nursing Process Implementation in Clinical Practice - Mohammed Salih Jasim; Younes K. Attia; Atheer Abd Ahmed (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): The nursing process (NP) is a systematic framework for delivering holistic, evidence-based, and patient-centered care, yet its consistent application remains limited in many clinical contexts. Background (Specific): In Iraq, nurses face systemic, organizational, and cultural barriers that compromise the effective use of the NP, despite its foundational role in nursing practice. Knowledge Gap: While prior studies have identified individual challenges, few have comprehensively examined barriers using mixed-method approaches that integrate both quantitative and qualitative perspectives. Aim: This study sought to identify and analyze the barriers hindering the implementation of the NP among nurses in Mosul through a sequential mixed-method design. Results: Quantitative findings from 500 nurses revealed that lack of knowledge and skills (78.4%), insufficient organizational support (86.2%), and inadequate training (77.0%) were major barriers, while qualitative interviews highlighted themes of poor interprofessional communication, cultural resistance to change, and resource shortages. Novelty: By combining statistical analysis with thematic insights, this research offers a multidimensional understanding of NP challenges, emphasizing the interplay between personal competencies and systemic constraints. Implications: The findings underscore the urgent need for targeted interventions in training, policy, and organizational support to strengthen NP implementation and improve patient outcomes in resource-limited healthcare systems. Highlights : Lack of knowledge, training, and organizational support are the main barriers. Mixed-methods approach reveals both statistical trends and thematic insights. Urgent need for targeted interventions to improve nursing practice and patient outcomes. Keywords: Nursing Process, Barriers, Organizational Support, Training, Patient Care